Characterization antibacterial constituent from Ficus deltoideusJack leaves - Suryati .; Hazli Nurdin; Dachriyanus .; Md Nordin Hj Lajis (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
An antibacterial constituent, has been isolated from Ficus deltoideus Jack leaves. Based on spectroscopic data (IR, 1H-NMR, 13 C NMR 1D and 2D and MS), the structure of this compound was identified as Olean-12en-3β-ol, (β-amyrin), C30H50O. This compound showed antibacterial activities against E. coli, B. subtilis and S. aureus. The minimum inhibition concentration (MIC) agains E. coli, B. subtilisand S. aureusare 230, 380 and 460 (µg/mL) respectively.Key words: Antibacterial activity,Ficus deltoideusJack, β-amyrin